Mitoni Tradition: Between Local Wisdom and Maqashid Shari'ah View - Nasrul Fatah; Syarifah Laili (Westscience Press, 2026)
Indonesian society is very thick with various traditions in their daily lives. Among the traditions that are still maintained and carried out is the mitoni tradition. This tradition is practiced by Javanese people or Javanese descendants, whether in Java or outside Java and across religions. It is not uncommon for the implementation of various traditions to be clashed with Islamic law, whether it is considered appropriate or not. So this paper tries to elaborate the mitoni tradition as local wisdom with the maqashid shari'ah approach. Using a qualitative-narrative research method, this research is based on literature data. This study found that the mitoni tradition historically originated from religious practices outside Islam with its various rituals. However, in the modern era, its implementation has undergone many changes and is identical to Islamic rituals, such as the recitation of Qur'anic verses, shalawat and Islamic versions of salvation prayers. In the perspective of maqashid shari'ah, this tradition can be accommodated in sharia as long as elements that have the potential to contain shirk are not implemented and replaced with more Islamic ones. This is because there are values of preserving religion, life, integrity and property that are in accordance with maqashid.